CNS involvement in V30M transthyretin amyloidosis: clinical, neuropathological and biochemical findings. Issue 2 (4th August 2014) - Maia, Luís F; Magalhães, Rui; Freitas, Joel; Taipa, Ricardo; Pires, Manuel Melo; Osório, Hugo; Dias, Daniel; Pessegueiro, Helena; Correia, Manuel; Coelho, Teresa
Abstract : Objectives: Since liver transplant (LT) was introduced to treat patients with familial amyloid polyneuropathy carrying the V30M mutation (ATTR-V30M), ocular and cardiac complications have developed. Long-term central nervous system (CNS) involvement was not investigated. Our goals were to: (1) identify and characterise focal neurological episodes (FNEs) due to CNS dysfunction in ATTR-V30M patients; (2) characterise neuropathological features and temporal profile of CNS transthyretin amyloidosis. Methods: We monitored the presence and type of FNEs in 87 consecutive ATTR-V30M and 35 non-ATTR LT patients. FNEs were investigated with CT scan, EEG and extensive neurovascular workup. MRI studies were not performed because all patients had cardiac pacemakers as part of the LT protocol. We characterised transthyretin amyloid deposition in the brains of seven ATTR-V30M patients, dead 3–13 years after polyneuropathy onset. Results: FNEs occurred in 31% (27/87) of ATTR-V30M and in 5.7% (2/35) of the non-ATTR transplanted patients (OR=7.0, 95% CI 1.5 to 33.5). FNEs occurred on average 14.6 years after disease onset (95% CI 13.3 to 16.0) in ATTR-V30M patients, which is beyond the life expectancy of non-transplanted ATTR-V30M patients (10.9, 95% CI 10.5 to 11.3). ATTR-V30M patients with FNEs had longer disease duration (OR=1.24; 95% CI 1.07 to 1.43), renal dysfunction (OR=4.65; 95% CI 1.20 to 18.05) and were men (OR=3.57; 95% CI 1.02 to 12.30). CNS transthyretin amyloidosis was already present 3 years after polyneuropathy onset and progressed from the meninges and its vessels towards meningocortical vessels and the superficial brain parenchyma, as disease duration increased. Conclusions: Our findings indicate that CNS clinical involvement occurs in ATTR-V30M patients regardless of LT. Longer disease duration after LT can provide the necessary time for transthyretin amyloidosis to progress until it becomes clinically relevant. Highly sensitive imaging methods are needed to identify and monitor brain ATTR. Disease modifying therapies should consider brain TTR as a target.